2011
DOI: 10.1111/j.1365-2443.2011.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Dmrta2 regulates neurogenesis in the telencephalon

Abstract: Although recent findings showed that some Drosophila doublesex and Caenorhabditis elegans mab-3 related genes are expressed in neural tissues during development, their functions have not been fully elucidated. Here, we isolated a zebrafish mutant, ha2, that shows defects in telencephalic neurogenesis and found that ha2 encodes Doublesex and MAB-3 related transcription factor like family A2 (Dmrta2). dmrta2 expression is restricted to the telencephalon, diencephalon and olfactory placode during somitogenesis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 45 publications
3
43
1
Order By: Relevance
“…Loss-of-function mutations in Dmrta2 have been linked with microcephaly in zebrafish, mice, and humans (7,(10)(11)(12)(13); however, the role and mechanism of action of Dmrta2 in the control of NPC maintenance and expansion have remained unknown until now. Recently, conditional Dmrta2 mutant mice (Dmrta2 fl/fl ;Emx1-cre) were created that delete Dmrta2 in cortical progenitors after cortical hem formation without impacting Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss-of-function mutations in Dmrta2 have been linked with microcephaly in zebrafish, mice, and humans (7,(10)(11)(12)(13); however, the role and mechanism of action of Dmrta2 in the control of NPC maintenance and expansion have remained unknown until now. Recently, conditional Dmrta2 mutant mice (Dmrta2 fl/fl ;Emx1-cre) were created that delete Dmrta2 in cortical progenitors after cortical hem formation without impacting Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Another site of expression and function of Dmrta2 has been found in the embryonic brain, however (9,10). Dmrta2 loss of function in zebrafish leads to significant reductions in cortical size, coupled with reduced neuronal numbers (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DMRT is homologous to the Drosophila doublesex gene, which, in addition to a role in sex determination, also functions in the development of neurons controlling sex-specific behavior (Rideout et al, 2007;Rideout et al, 2010). In vertebrate embryos, DMRT genes mark anterior neural regions, including the nasal placode and presumptive forebrain (Winkler et al, 2004;Huang et al, 2005;Veith et al, 2006;Wen et al, 2009;Yoshizawa et al, 2011). In Ciona, DMRT is first expressed at the 64-cell stage in the a7.10, a7.9 and a7.13 blastomeres, which are progenitors of the anterior neural plate (a-line, rows III-VI) (Imai et al, 2006;Tresser et al, 2010).…”
Section: Research Articlementioning
confidence: 99%
“…In the simple chordate Ciona, Dmrt1, the ortholog of vertebrate Dmrt4-5, is essential for the development of anterior neural plate derivatives (Tresser et al 2010). In zebrafish, a recent analysis of a Dmrt5 (Dmrta2) mutant has revealed that it regulates neurogenesis in the telencephalon (Yoshizawa et al 2011). The role of Dmrt genes in mammalian forebrain development is unknown.…”
Section: Introductionmentioning
confidence: 99%